IoT-Enabled Community Care for Ageing-in-Place: The Singapore Experience - Hwee Pink Tan (IAES Indonesia Section, 2020)
The paradigm of ageing-in-place - where the elderly live and age in their own homes, independently and safely, with care provided by the community - is compelling, especially in societies that face both shortages in institutionalized eldercare resources, and rapidly ageing populations. When the number of elderly who live alone rises rapidly, support and care from their communities become increasing crucial. Internet of Things (IoT) technologies. They can become the fundamental enabler for smart community eldercare. In this presentation, I would like to share our experiences and learnings gathered from large-scale deployments of IoT systems in in-home and community spaces that elderly living alone interact with, focusing on the key insights as well as operational and usability aspects of such systems.